Socioeconomic Status and the Digital Divide in AI-Driven Learning Environments - Jayrome L. Nuñez; Jomar M. Urbano; Denise Kristine S. Ong; Lucky Jhon D. Tiongco (Universitas Dharma Wacana, 2026)
This study examined the socioeconomic divide in the use of artificial intelligence (AI) in learning environments among university students in selected universities in the Philippines. Specifically, it explored how socioeconomic factors such as access to devices, internet reliability, affordability, technical limitations, and family support influence students’ use and experience of AI-driven learning tools. The study used a quantitative, non-experimental, cross-sectional, descriptive research design. Data was collected through a structured questionnaire administered to 204 university students and were analyzed using frequency and percentage distribution. The findings revealed that most respondents recognized the usefulness of AI in learning, particularly in helping them understand lessons and complete academic tasks. A majority of students also reported frequent access to personal devices and relatively reliable internet connectivity. However, the results showed that significant barriers remain. More than half of the respondents identified the cost of devices and internet services as a household challenge, while many also reported technical limitations such as slow internet and outdated devices. Family support was found to be moderate and uneven, suggesting that students do not experience the same level of assistance in using AI tools for academic purposes. Although many students expressed confidence in using AI, their overall experience was only moderately positive. The study concludes that the digital divide in AI-driven learning environments is not only about physical access to technology, but also about the quality, affordability, and consistency of access and support. It recommends that higher education institutions adopt inclusive strategies that improve digital access, strengthen student support, and ensure equitable opportunities for using AI in learning.